Kemampuan Pengunaan Media Panggung Boneka Interkatif Oleh Guru Untuk Meningkatkan Minat Belajar Anak Pendidikan Usia Dini - Rosmey Meriaty Br.Sormin (Institut Agama Kristen Negeri Tarutung, 2020)
The purpose of this paper is to determine how the ability of PAUD teachers in using the Puppet Stage to increase interest in learning PAUD children. PAUD teachers' abilities include storytelling skills, the ability to mobilize puppet stage skills, voice intonation skills, and the Psychological Needs ability of PAUD children. With interest in learning, PAUD children have good character knowledge. The research method used is a quantitative method, by analyzing several literatures